FRI0302 Elevated cysteine-rich protein 61 in systemic lupus erythematosus-associated pulmonary arterial hypertension. (15th June 2017) - Fan, Y; Qian, J; Hao, Y; Li, M; Gao, L; Zeng, X; Zhang, Z
Abstract : Background: Pulmonary arterial hypertension (PAH) is a complex and devastating complication of connective tissue diseases that leads to severe morbidity and mortality.Unlike in Caucasians, it is systemic lupus erythematosus that recognized as the the major underlying cause of CTD associated PAH in Asian countries, especially in China [1]. Early diagnosis and intervention is vital for better long-term outcome in SLE-PAH patients.Previous study has demonstrated Cysteine-rich protein 61 (Cyr61) was highly expressed in SLE patients [2].However, the role of Cyr61 in pulmonary arterial hypertension (PAH) remains unknown. Objectives: To explore the value of Cyr61 for PAH in SLE patients by comparing the plasma Cyr61 levels in SLE patients with/without PAH. Methods: Plasma samples from two tertiary medical centers were obtained from 54 patients with definite SLE-PAH, 52 age, gender and SLEDAI matched SLE patients without PAH, and 54 age and gender matched healthy controls. Plasma Cyr61 concentration was measured by enzyme-linked immunosorbent assay. Results: Plasma Cyr61 concentration in SLE-PAH patients was significantly higher than the matched SLE patients and healthy controls (median (IQR): 172.5 (143.8, 218.2), 124.9 (104.1, 154.7), 58.17 (28.9, 80.4) respectively, P<0.001) (Figure1 ). The sensitivity and specificity of Cyr61 in predicting the presence of PAH in entire SLE patients were 79.6% and 67.3%. Receiver operating characteristic curve analysis showed the area under the curve was 0.757 (95% CI: 0.662–0.852), with 140.6 pg/ml as the cut off concentration (Figure2). Further multivariate logistic regression analyses revealed high Cyr61 level (>140.6) is an independent risk factor for SLE patients to develop PAH (OR:7.822 (95% CI: 2.224–41.138)) (Table 1 ). Additionally, weak to moderate positive correlations were observed between Cyr61 concentration and serositis, hematological involvement, red blood cell distribution width, right ventricular systolic pressure and right ventricular diameter measured by echocardiography in entire SLE population. Conclusions: Plasma Cyr61 level was significantly higher in SLE-PAH patients than SLE patients without PAH. Cyr61 may be used as a biomarker for PAH complication in SLE patients. References: Hao, Y.J., et al., Connective tissue disease-associated pulmonary arterial hypertension in Chinese patients. European Respiratory Journal, 2014. 44(4): p. 963–972. Lin, J., et al., Serum Cyr61 is associated with clinical disease activity and inflammation in patients with systemic lupus erythematosus. Medicine (Baltimore), 2015. 94(19): p. e834. Disclosure of Interest: None declared